The effect of vesicular-arbuscular mycorrhizal fungi on growth of peppermint - M.L. GUPTA; S. KUMAR, ABDUL-KHALIQ*, (Indian Phytopathology, 2002)
Influence of three species of vesicular-arbuscular mycorrhizal (VAM) fungi, namely, Glomus aggregatum, G.fasciculatum and G. mosseae was studied on the growth of peppermint (Mentha Piperita L.) under glasshouse conditions. Colonization of VAM fungi in roots because of symbiosis, was highest in G. fasciculatum inoculated plants (67.7%). Consequently, the three VAM fungi were found to enhance mineral uptake, specifically phosphorus (P), potassium (K) and Zinc (Zn). However, a significant rise in uptake of P by 128.6%, K 120.4% and Zn 82.7% were recorded when plants were inoculated with G. fasciculatum. The experimental studies revealed that G. fasciculatum enhanced the highest shoot biomass goes upto 145.3% followed by G. aggregatum (131.1%) and G. mosseae (87.8%) in comparison to control treatment. It is also apparent from the results that per cent essential oil contents in shoot tissues from unit weight of herb yield did not increase significantly in comparison to control. The experimental findings indicated the potential use of efficient VA-mycorrhizal fungi for improving the. growth and productivity of M. piperita.